Mean motion resonances among the small satellites of Saturn and Pluto - Santana, Thamiris de [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
This work is organized into three parts. In Part I, we present a quick review of Saturn’s satellites Prometheus and Pandora lags problem. We analyzed the lags ratio Q = ∆λpro ∆λpan through the conservation of the angular momentum, that implies the ratio of the lags due to this mutual interaction must be almost constant. However, we found that the values obtained using observational data fit Qobs does not agree with the assumed masses mpan/mpro = 0.56 and is not even nearly constant. It presents a robust linear increasing rate given by Qobs(t) = 0.667 + 0.013t, with t given in years. In this way, we show that only the gravitational interaction between the satellites does not fully explain the lags values. This indicates that a non-mutual mechanism should provoke at least a mean motion changing of 0.45◦/year, also affecting Prometheus or Pandora, contributes to the lag values. In Part II, we performed the astrometry of the satellite Daphnis using the Caviar software in a selected set of images from the ISS-NAC camera of Cassini spacecraft. Daphnis’ astrometry of all Cassini mission period showed that Daphnis had changed its orbit twice. So, we have investigated the stability of Daphnis’ orbit by implemented numerical simulations considering Saturn plus five satellites: Daphnis, Atlas, Prometheus, Pandora, and Mimas and computing the evolution of the Fast Lyapunov Indicator FLI. We showed that Daphnis is on a chaotic orbit with a Lyapunov time of ∼13 years. By investigating possible resonances between Daphnis and other satellites, we found that Prometheus and Atlas with 129:125 and 157:155 mean motion resonant angles, respectively, present some features that could indicate chaos. Additionally, we found that when Prometheus and Atlas are not included in the numerical simulation, Daphnis’ orbit became regular, reinforcing the suggestion that both satellites are playing a role in Daphnis’ chaotic behavior. In Part III, we presented a study of the origin of resonance between the satellites of Pluto. We performed N-body numerical simulations considering the small satellites and Charon evolving under the influence of the tidal force due of Pluto on Charon. Using the J2 effective approach, we showed that the small satellites could be captured into the 3:1, 4:1, 5:1, 6:1 mean motion resonances with Charon. Even for the case of the 5:1 and 6:1 mean motion resonances, it was possible to achieve a capture only when some non-zero eccentricity was added to Charon. Moreover, the 3:1 mean motion resonance between Charon and Styx, in inclination, was the easiest to happen. To find the three body resonance 3:5:2 among Styx, Nix, and Hydra, we looked for two particular resonances among them: 2:1 between Styx and Hydra and 5:4 between Nix and Styx. We have found parameters that allow the capture of the small bodies into the exact two 2-body resonant arguments we need, but not at the same time. In this way, we perceive that we are close to finding the right parameters to represent all the paths of the Pluto’s moons from their past to the current intriguing configuration. Some different ideas may be tested to bring us to the present scenario

Este trabalho está dividido em três partes. Na Parte I é apresentada uma breve revisão sobre o problema da defasagem dos satélites Prometeu e Pandora de Saturno. Analisamos a razão entre as defasagens Q = ∆λpro ∆λpan através da conservação do momento angular, o que implica que o fator Q devido à perturbação deve ser praticamente constante. Contudo, verificou-se que os valores ajustados a partir de dados observacionais Qobs não está de acordo com a razão de massas assumidas mpan/mpro = 0.56 e também não tem um comportamento constante. Verificou-se que há um aumento linear dado por Qobs(t) = 0.667 + 0.013t, com t dado em anos. Desta forma mostrou-se que somente a interação gravitacional entre os satélites não explica completamente os valores das defasagens. Isso indica que algum mecanismo não-mútuo deve causar pelo menos uma alteração no movimento médio de 0.45◦/ano de Prometeu ou Pandora e contribui para os valores das defasagens. Na Parte II é realizada a astrometria do satélite Daphnis utilizando o software Caviar para um conjunto selecionado de imagens da câmera ISS-NAC da sonda Cassini. A astrometria do satélite para todo o período da missão Cassini mostrou que Daphnis mudou sua órbita duas vezes. Assim, foi investigada a estabilidade orbital de Daphnis através de simulações numéricas considerando Saturno e cinco satélites ( Daphnis, Atlas, Prometeu, Pandora e Mimas) e calculando a evolução do Indicador Rápido de Lyapunov. É mostrado que Daphnis está em uma órbita caótica com um tempo de Lyapunov de ∼22 anos. Investigando possíveis ressonâncias entre Daphnis e outros satélites, verificou-se que as ressonâncias 129:125 e 157:155 com Prometeu e Atlas, respectivamente, apresentam algumas características que podem indicar caos. Adicionalmente, em simulações numéricas sem os satélites Prometeu e Atlas a órbita de Daphnis permaneceu regular, reforçando a idéia que são estes dois satélites que tem um papel relevante no comportamento caótico de Daphnis. Na Parte III é apresentado um estudo da origem das ressonâncias entre os satélites de Plutão. Foram realizadas simulações numéricas do problema de N-corpos considerando os pequenos satélites e Caronte, incluindo a migração de Caronte devido à força de maré. Utilizando a abordagem do J2 efetivo mostrou-se que os pequenos satélites podem ser capturados nas ressonâncias de movimento médio 3:1, 4:1, 5:1, 6:1 com Caronte. Para os casos das ressonâncias 5:1 e 6:1 foi possível obter uma captura somente quando uma excentricidade não nula foi considerada para Caronte. Além disso, a ressonância de movimento médio 3:1 em inclinação entre Caronte e Estige é a mais fácil de ocorrer. Para encontrar a ressonância de três corpos 3:5:2 entre Estige, Nix e Hidra procurou-se por duas ressonâncias específicas entre os satélites: 2:1 entre Estige e Hidra, e 5:4 entre Nix e Estige. Foram encontrados parâmetros que permitem a captura dos pequenos satélites exatamente com os argumentos das ressonâncias de dois corpos necessárias, porém não simultaneamente. Desta forma, sabe-se que é um caminho promissor para determinação dos parâmetros para representar a evolução dos satélites de Plutão até suas posições atuais.
Ressonâncias de movimento médio entre pequenos satélites de Saturno e Plutão
Keywords: satellites; Planets; orbits; astrometry; satélites; planetas; órbitas; astrometria; mecânica celeste; celestial mechanics; mean motion resonances